Designing the Future of Islamic education: Opportunities, Challenges, and Characteristics of Effective Planning - Dennis Haruna; Ayunda Salsabila; Januar Januar (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2024)
The digital era has brought great changes in the world of Islamic religious education, increasing the effectiveness and efficiency of educational activities with the presence of digital devices. However, another significant challenge is the threat of radicalism that can influence students' thinking and attitudes. Therefore, Islamic education must be able to equip students with a moderate and tolerant understanding of religion to prevent the spread of extreme views. This research aims to provide a clear picture of the challenges and opportunities facing Islamic education in the modern era, as well as present the characteristics of effective planning in facing the future. Thus, this research is expected to be a reference for stakeholders in designing Islamic education strategies that are adaptive and responsive to changing times, so as to produce a generation that is characterized, knowledgeable, and ready to face various global challenges. This research uses library research method to collect and analyze information from various written sources relevant to the topic discussed. The results show that Islamic education must be set on fundamental values such as tawhid, imitating the Prophet, and making the Qur'an and Sunnah the main sources of learning. In order to advance Islamic education, all parties-including educators, parents, communities and governments-are expected to play an active role. Active participation and collaboration between various stakeholders will ensure that Islamic education is not only relevant but also able to withstand future challenges. Based on the findings of this study, several policy recommendations can be proposed. By following these recommendations, it is hoped that Islamic education can continue to grow and make a positive contribution to society and the nation.